TRANSFORMATION OF LOCAL CULTURAL WISDOM OF CIREUNDEU TRADITIONAL VILLAGE AS CIVIC CULTURE - Nurdin, Melda Agriya Ningsih; Ramadhani, Syahrul; Abdillah, Abdillah (Jurnal Masyarakat dan Budaya, 2025)
This research analyzes how the Cireundeu Traditional Village community can try to preserve their customs and maintain their culture as the national culture of Indonesian citizenship. The method used in this study is qualitative with a case study approach, and data collection is obtained through observation, interviews, and documentation. The result of this research is the process of cultural transformation of the indigenous people of Kampung Cireundeu as a reference for the culture of society in Indonesia. Culture in the Cireundeu Traditional Village encourages people to live, respect the environment, and have interactive dialogues in resolving conflicts so that it becomes a socio-cultural transformation in Indonesia.